MicroRNAs and Potential Targets in Osteosarcoma: Review - Sampson, Valerie B.; Yoo, Soonmoon; Kumar, Asmita; Vetter, Nancy S.; Kolb, E. Anders (Frontiers in Pediatrics, 2015)
Osteosarcoma is the most common bone cancer in children and young adults. Surgery and multi-agent chemotherapy are the standard treatment regimens for this disease. New therapies are being investigated to improve overall survival in patients. Molecular targets that actively modulate cell processes such as cell-cycle control, cell proliferation, metabolism and apoptosis, have been studied, but it remains a challenge to develop novel, effective targeted therapies to treat this heterogeneous and complex disease. MicroRNAs (miRNAs) are small noncoding RNAs that play critical roles in regulating cell processes including growth, development and disease. miRNAs function as oncogenes or tumor suppressors to regulate gene and protein expression. Several studies have demonstrated the involvement of miRNAs in the pathogenesis of osteosarcoma with the potential for development in disease diagnostics and therapeutics. In this review, we discuss the current knowledge on the role of miRNAs and their target genes and evaluate their potential use as therapeutic agents in osteosarcoma. We also summarize the efficacy of inhibition of oncogenic miRNAs or expression of tumor suppressor miRNAs in preclinical models of osteosarcoma. Recent progress on systemic delivery as well as current applications for miRNAs as therapeutic agents has seen the advancement of miR-34a in clinical trials for adult patients with non-resectable primary liver cancer or metastatic cancer with liver involvement. We suggest a global approach to the understanding of the pathogenesis of osteosarcoma may identify candidate miRNAs as promising biomarkers for this rare disease.